From love for nature to sustainable value creation: A Gioia-based study of ecopreneurial transformation in SMEs - Indra Lukmana Putra; Sudarmiatin Sudarmiatin; Agus Hermawan; Wening Patmi Rahayu (Novera: Journal of Economics and Business, 2026)
Small and medium-sized enterprises (SMEs) face increasing pressure to create economic value without intensifying environmental problems, yet the process through which ecological concern becomes entrepreneurial action remains insufficiently understood. This study aims to examine how love for nature develops into an ecopreneurial orientation, translates into green business innovation, and generates sustainable value. An exploratory qualitative approach was employed with 27 informants involved in seven groups of green businesses in East Java, Indonesia, using the Gioia methodology for data analysis. The findings indicate that ecopreneurship develops through ecological orientation, entrepreneurial translation, and value creation and change. This process transforms Love for Nature into Ecological Values, Ecopreneurial Motivation, Green Business Innovation, Community Value Creation, and Sustainable Change. The study contributes an Ecopreneurship Transformation Model that positions ecological concern as the foundation for creating economic, social, and environmental value through entrepreneurial action. Abstrak Usaha Mikro, Kecil, dan Menengah (UMKM) menghadapi tuntutan untuk menghasilkan nilai ekonomi tanpa memperbesar tekanan terhadap lingkungan, tetapi proses yang mengubah kepedulian ekologis menjadi tindakan kewirausahaan masih kurang dipahami. Penelitian ini bertujuan menganalisis bagaimana kecintaan terhadap alam berkembang menjadi orientasi ecopreneurship, diterjemahkan ke dalam inovasi bisnis hijau, dan menghasilkan nilai berkelanjutan. Penelitian menggunakan pendekatan kualitatif eksploratif terhadap 27 informan yang terlibat dalam tujuh kelompok usaha hijau di Jawa Timur, dengan analisis data menggunakan Gioia methodology. Hasil penelitian menunjukkan bahwa ecopreneurship berlangsung melalui rangkaian orientasi ekologis, penerjemahan kewirausahaan, serta penciptaan nilai dan perubahan. Proses tersebut membentuk transformasi dari Love for Nature menuju Ecological Values, Ecopreneurial Motivation, Green Business Innovation, Community Value Creation, dan Sustainable Change. Penelitian ini menghasilkan Ecopreneurship Transformation Model yang menempatkan kepedulian ekologis sebagai fondasi penciptaan nilai ekonomi, sosial, dan lingkungan secara berkelanjutan.